2012
DOI: 10.1071/ah11076
|View full text |Cite
|
Sign up to set email alerts
|

Medical Assessment Units and the older patient: a retrospective case-control study

Abstract: Eighty-nine patients were studied; 47 in the MAU group and 42 in the non-MAU group. The MAU cohort was significantly older (84.1 ± 7.9 years v. 80.4 ± 7.8 years, respectively, P=0.03); and had shorter ED LOS (4.9 ± 3.0h v. 6.5 ± 2.8h, P=0.012). Overall hospital LOS did not differ except for patients with 'cellulitis', (5.7 ± 4.9 days for MAU cohort v. 14.8 ± 6.8 days for non-MAU cohort, P=0.022). There was no significant difference in mortality, readmission rate or discharge destination. Conclusions. The MAU c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…11 Observation wards and short-stay units have added new streaming options for ED patients who require a short period of admission for clinical observation and intervention. 2 ED short-stay units have traditionally been reserved for patients who are most likely to be discharged within 24 h. Medical admission and assessment units have become commonplace in many hospitals as a conduit for medical admissions from the ED 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Observation wards and short-stay units have added new streaming options for ED patients who require a short period of admission for clinical observation and intervention. 2 ED short-stay units have traditionally been reserved for patients who are most likely to be discharged within 24 h. Medical admission and assessment units have become commonplace in many hospitals as a conduit for medical admissions from the ED 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Of them, only five studies demonstrated statistical significance in lowering ED use or ED length of stay (LOS) 27 31 32 36 37. None of them used RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the five interventions featured multidisciplinary team and care planning,36 37 and another two interventions included follow-up visits 31 32. However, unlike community-based interventions, these hospital-based strategies were most characterised by risk screening and geriatric assessment for the purpose of identifying potential risk factors and unresolved problems,27 32 36 37 and discharge planning and referral coordination 31 32. Most of the interventions were relatively long-term, with only two being shorter than 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GP admissions not targeted through GPSU increased by 3.99 per day (2.64 to 5.33). Modest reduction in GP admissions to MAU but no reduction in number of GP admissions to hospital wards.Before and after design.Ong et al, 2012, Australia [13]Patients ≥65 years. Diagnosis groups: falls and gait disorder, COPD, other major respiratory diseases, cellulitis.…”
Section: Methodsmentioning
confidence: 99%